Attenuated poxviruses expressing a synthetic HIV protein stimulate HLA-A2-restricted cytotoxic T-cell responses - Didierlaurent, Arnaud (2004)
Efficient HIV vaccines have to trigger cell-mediated immunity directed against various viral antigens. However little is known about the breadth of the response induced by vaccines carrying multiple proteins. Here, we report on the immunogenicity of a construct harbouring a fusion of the HIV-1 IIIB gag, pol and nef genes (gpn) designed for optimal safety and equimolar expression of the HIV proteins. The attenuated poxviruses, MVA and NYVAC, harbouring the gpn construct, induced potent immune responses in conventional mice characterised by stimulation of Gpn-specific IFN-γ-producing cells and cytotoxic T cells. In HLA-A2 transgenic mice, recombinant MVA elicited cytotoxic responses against epitopes recognised in most HLA-A2+ HIV-1-infected individuals. We also found that the MVA vaccine triggered the in vitro expansion of peripheral blood cells isolated from a HIV-1-seropositive patient and with similar specificity as found in immunised HLA-A2 transgenic mice. In conclusion, the synthetic HIV polyantigen Gpn delivered by MVA is immunogenic, efficiently processed and presented by human MHC class I molecules.